2021
DOI: 10.37433/aad.v2i3.139
|View full text |Cite
|
Sign up to set email alerts
|

The EVAL framework: Developing impact evaluation scholars

Abstract: The complexities of food, agriculture, natural resources, and human sciences (FANH) programs and   projects require faculty to write and secure funding in addition to mastering skills such as evaluation competencies that integrate abilities in quantitative and qualitative research methods and evaluation theory and practice. The EVAL Framework was developed to advance skill development among FANH graduates to include these competencies and increase the pipeline of students who have the essential skills needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Early majority adopters have similar characteristics to early adopters, with the principal difference that the early majority members did not have leadership roles (Strong et al) [22]. Another dissimilarity is early majority members do not possess as much aversion to risk as innovators and early adopters within social systems.…”
Section: Introductionmentioning
confidence: 99%
“…Early majority adopters have similar characteristics to early adopters, with the principal difference that the early majority members did not have leadership roles (Strong et al) [22]. Another dissimilarity is early majority members do not possess as much aversion to risk as innovators and early adopters within social systems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, DHS surveyors and researchers should evaluate how target populations with every aspect receive the same public messages differently. Building trust in the target areas is indispensable to public health interventions [36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies indicated that effective nutrition education inventions may include diet counseling, increasing access to health professionals, and distributing newsletters about healthy eating, can improve nutrition knowledge and result in positive change of behavior across entire communities [72,78]. The benefits of school-based and adult consumer education programs should be evaluated holistically to document the impact of these educational programs [79].…”
Section: Discussionmentioning
confidence: 99%